Sinergi Financial Literacy, Fintech, dan Financial Behaviour dalam Mendorong Kinerja UMKM - Annisa Kusumawati; R. Andro Zylio Nugraha; Arief Nurrahman; Agatha Saputri; Caesar Rosyad Achmadi; Muhammad Harfiansyah Makarim (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study aims to evaluate the influence of financial literacy, financial technology, and financial behavior on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Sleman Regency, Yogyakarta Special Region. The approach used is descriptive quantitative, with primary data obtained through distributing questionnaires to 215 active MSME players. Data analysis was conducted using the Partial Least Square (PLS) method to assess the relationship between variables. The research findings indicate that financial literacy and financial behavior have a positive and significant impact on the financial performance of MSMEs. A good level of financial literacy helps businesses in preparing thorough financial reports, managing risks, and making the right financial decisions. Meanwhile, financial behaviors such as budget management, transaction recording, and regular financial evaluation have been proven to improve the stability and growth of business finances. On the other hand, the use of financial technology did not show a significant effect on financial performance, which may be due to the low level of understanding and access to such technology among MSME actors. The results of this study emphasize the importance of comprehensive counseling and training on financial literacy and the use of financial technology to improve the competitiveness and sustainability of MSMEs in the face of increasingly competitive market challenges.